The Effect of Mind Mapping Technique on Poetry Writing Skills Elementary School Students - Dina Dahliana (International Journal of Educational Dynamics, 2019)
This study aims to examine the Effect of Mind Mapping Techniques on Poetry Writing Skills of students in elementary schools. This research is an experimental research type Quasi Experimental Design with the design of Nonequivalent Control Group Design. Based on the results of the pretest the average value of the experimental class 60 was obtained and the average value of the control class was 64.2. From the results of the comparison of the two sample classes obtained a difference in value of 3.7, it can be concluded that there is no significant difference in the value of the pretest of both classes, meaning that both classes have the same initial ability. Then learning is done using mind mapping techniques in the experimental class and learning without mind mapping techniques in the control class. After learning was given later in both classes posttest was conducted. For the experimental class the average value is 82 and for the control class the average value is 77.5. From the results of testing the hypothesis with a significant level of 0.05 obtained a significant value of 0,000 because of sig. <α, the hypothesis is accepted, so it can be concluded that there is an effect of using mind mapping techniques on students' poetry writing skills in elementary schools. Keywords: Mind Mapping Techniques, Poetry, Writing Skills